Economic evaluation of 18F-FDG PET/CT, MRI and CE-CT in selection of colorectal liver metastases eligible for ablation: a cost-effectiveness analysis - Schnitzer, Moritz Ludwig; Buchner, Janine; Biechele, Gloria; Grawe, Freba; Ingenerf, Maria; Münchhausen, Niklas, Freiherr von; Kaiser, Clemens G.; Kunz, Wolfgang G.; Froelich, Matthias F.; Schmid-Tannwald, Christine; Rübenthaler, Johannes (European journal of radiology, 2023)
Objectives - Colorectal cancers (CRC) are among the world's most prevailing cancer entities. In a third of all cases, the patients have already developed distant metastases - mainly in the liver - at the time of detection. Colorectal liver metastases (CRLM) can be treated by surgical resection or, as is possible in most cases, by percutaneous ablation. For selecting the liver metastases eligible for radiofrequency ablation (RFA) or microwave ablation (MWA), the common imaging modalities are magnetic resonance imaging (MRI), positron emission tomography/computed tomography (PET/CT), and contrast-enhanced computed tomography (CE-CT). This study aims to evaluate those imaging modalities for selecting liver lesions eligible for ablation according to their long-term cost-effectiveness. - Materials and methods - A Markov model was applied, calculating quality-adjusted life years (QALYs) and accumulative costs for every diagnostic strategy, according to predefined input parameters obtained from published research. Further, sensitivity analyses were executed to prove the certainty of the calculations by running Monte-Carlo simulations with 30,000 reiterations. The Willingness-to-pay (WTP) is at $ 100,000. All calculations are based on the U.S. healthcare system. - Results - CE-CT caused cumulative costs of $ 31,940.98 and 8,99 QALYs, whereas MRI caused $ 32,070.83 and 9,01 QALYs. PET/CT caused cumulative costs of $ 33,013.21 and 8,99 QALYs. - Conclusion - In conclusion, according to our analysis, MRI is the most cost-effective strategy for detecting liver metastases eligible for ablation and therefore should be seen as the gold standard.
Online verfügbar: 30. März 2023, Artikelversion: 31. März 2023
Gesehen am 08.08.2024